2021
DOI: 10.3758/s13420-021-00500-6
|View full text |Cite
|
Sign up to set email alerts
|

Space, feature, and risk sensitivity in homing pigeons (Columba livia): Broadening the conversation on the role of the avian hippocampus in memory

Abstract: David Sherry has been a pioneer in investigating the avian hippocampal formation (HF) and spatial memory. Following on his work and observations that HF is sensitive to the occurrence of reward (food), we were interested in carrying out an exploratory study to investigate possible HF involvement in the representation goal value and risk. Control sham-lesioned and hippocampal-lesioned pigeons were trained in an open field to locate one food bowl containing a constant two food pellets on all trials, and two vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…It has to be also considered that stimulus discrimination in the HF of pigeons is further highly associated with a spatial component ( Coppola et al, 2014 ). Further, a new study suggested that the function of the HF in memorizing properties, or more precisely probabilities of reward occurrences, seems to be associated with encoding of the spatial location ( Sizemore et al, 2021 ). Thus, this might also support the theory that a reduction of GRIN2B is more correlated to global behavioral learning phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…It has to be also considered that stimulus discrimination in the HF of pigeons is further highly associated with a spatial component ( Coppola et al, 2014 ). Further, a new study suggested that the function of the HF in memorizing properties, or more precisely probabilities of reward occurrences, seems to be associated with encoding of the spatial location ( Sizemore et al, 2021 ). Thus, this might also support the theory that a reduction of GRIN2B is more correlated to global behavioral learning phenomena.…”
Section: Discussionmentioning
confidence: 99%